Perkembangan Tata Guna Lahan Ditinjau Dari Historis Kelelawar Sebagai Nilai Simbol di Kecamatan Lalabata - Agusanjaya Agusanjaya; Nursyam AS; Fadhil Surur (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2020)
The existence of bats in the urban area of Soppeng Regency not only had a mystery, but also was a unique characteristic in that area. The bats still exist even the city was developed rapidly. This study was aimed to study the effect of bat habitat on land use development and to understand the direction of land use development in maintaing the sustainability of the bat's historical value. Desctiptive analysis and linear regression methods were used in this research. The results showed that the development of the city had linear pattern which follows the direction of the road so that the city was not centralized in Watansoppeng. The linear regression result showed that the population affect the development of land use in the District of Lalabata, Soppeng Regency. The population was more dominant to build outside the city in order to converse the habitat of bats.